Agency in schizophrenia and autism: a systematic review - Tan, Denise P. W.; Carter, Olivia; Marshall, Darcy-Rose; Perrykkad, Kelsey (Frontiers in Psychology, 2023)
Introduction Previous research suggests that altered experiences of agency are an underlying vulnerability in both schizophrenia and autism. Here, we explore agency as a potential transdiagnostic factor by conducting a systematic review of existing literature investigating agency in autism and schizophrenia individually and together. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we conducted three systematic searches on PsycINFO, Embase, Medline, PubMed and Web of Science to identify studies that investigated (1) agency in schizophrenia, (2) agency in autism, and (3) agency in both schizophrenia and autism. Results A total of 31 articles met eligibility criteria for inclusion and data extraction, with 24 measuring agency in schizophrenia, 7 investigating agency in autism, and no articles comparing the two. Results show that, compared to control populations, agency is significantly different in every identified schizophrenia study and generally not significantly different in autism. Discussion Importantly, we identified a lack of studies using common tasks and a disproportionate number of studies investigating different dimensions of agency across the two conditions, resulting in limited grounds for valid comparison. Systematic review registration Prospero, CRD42021273373.